1992
DOI: 10.1161/01.cir.85.1.391
|View full text |Cite
|
Sign up to set email alerts
|

A definition of the intima of human arteries and of its atherosclerosis-prone regions. A report from the Committee on Vascular Lesions of the Council on Arteriosclerosis, American Heart Association.

Abstract: T his report is a concise review of current knowledge of the structure and function of the intima of the aorta and the major distributing arteries. The main purpose of the review is to delineate normal arterial intima from atherosclerotic lesions and, in particular, to distinguish physiological adaptations from atherosclerotic increases in intimal thickness. To characterize normal intima, including the adaptive intimal thickenings, some of which represent locations in which atherosclerotic lesions are prone to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
200
0
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(219 citation statements)
references
References 170 publications
(9 reference statements)
10
200
0
7
Order By: Relevance
“…If we may assume that enzymatic degradation and fusion of lipid particles are essentially synonymous,10 our findings are in perfect accordance with the recently published electron micrographs of isolated extracellular lipid particles from aortic valves 26. Compared with the histological structure of adaptive intimal thickening of human arteries prone to atherosclerotic lesion development,27 the composition of the human aortic valve cusp with the fibrosa suffused with insudated lipoproteins is quite different. This dense matrix might favor entrapment of insudated lipoproteins counteracting sufficient statin effects.…”
Section: Discussionsupporting
confidence: 87%
“…If we may assume that enzymatic degradation and fusion of lipid particles are essentially synonymous,10 our findings are in perfect accordance with the recently published electron micrographs of isolated extracellular lipid particles from aortic valves 26. Compared with the histological structure of adaptive intimal thickening of human arteries prone to atherosclerotic lesion development,27 the composition of the human aortic valve cusp with the fibrosa suffused with insudated lipoproteins is quite different. This dense matrix might favor entrapment of insudated lipoproteins counteracting sufficient statin effects.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, haemoglobin possesses some properties that make it a good candidate for being a cause of diabetic endothelial dysfunction by this mechanism. It is sensitive to changes in glycaemic concentrations [27], it circulates freely in plasma in nanomolar concentrations [7] and it can penetrate into the vascular wall in non-pathological circumstances [30,31]. Very recently it has been shown that endothelial cells are able to incorporate cell-free haemoglobin, creating a new way for circulating haemoglobin to be in close contact with NO [32].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Five to ten per cent of coronary arteries of children aged 2-15 years show fibrous plaques, and it is generally believed that they evolve from an initial fatty streak. 3 Over the last 20 years, the development of noninvasive methods has allowed to assess in vivo abnormalities in vascular structure and function of young subjects at cardiovascular risk. [4][5][6] In particular, carotid intima-media thickness (IMT) is commonly used as a measure of preclinical atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%